Peran Orang Muda Katolik dalam Kehidupan Menggereja di Kota Malang - Simanjorang, Sandro (Perspektif, 2019)
The yout his the future of the nation, the state, and the church. Meaning, the presence of this generation is expected to offer a great impact for the whole society (nation, state, church). In Malang, the second largest city for students after Yogyakarta, there are plenty of youth. They come into the city from all parts of the country for higher education.The considerable amount of this generation in the city gives a great contribution for the church in particular. This article tries to explore their contribution, especially those who are Catholics, for the missional life of the church in the city.